An extended car-following model accounting for the average headway effect in intelligent transportation system - Kuang, Hua; Xu, Zhi-Peng; Li, Xing-Li; Lo, Siu-Ming (Physica A, 2017)
In this paper, an extended car-following model is proposed to simulate traffic flow by considering average headway of preceding vehicles group in intelligent transportation systems environment. The stability condition of this model is obtained by using the linear stability analysis. The phase diagram can be divided into three regions classified as the stable, the metastable and the unstable ones. The theoretical result shows that the average headway plays an important role in improving the stabilization of traffic system. The mKdV equation near the critical point is derived to describe the evolution properties of traffic density waves by applying the reductive perturbation method. Furthermore, through the simulation of space–time evolution of the vehicle headway, it is shown that the traffic jam can be suppressed efficiently with taking into account the average headway effect, and the analytical result is consistent with the simulation one. •A new car-following model is proposed by considering the average headway effect of preceding vehicles group in ITS environment.•Linear analysis is carried out to study the stability of traffic flow.•The mKdV equation can be derived by using the reductive perturbation method to describe the density wave of traffic jam.•The results show that the average headway effect can efficiently suppressed the emergence of traffic jamming.